Use of phase change materials microcapsules in aerial lime and gypsum mortars - Cunha, Sandra Raquel Leite (2011)
Presently, the concerns related to the buildings energy consumption are greater, emerging in this way the need to incorporate materials in the construction products which aim the improvement of the energetic efficiency f buildings. Therefore, the application of phase change materials appears as a possible solution in an attempt to solve, or at least minimize, the massive energetic consumption related with buildings. This analysis aims the understanding of the influence of microcapsules of phase change materials (PCM) on lime and gypsum mortars which should present a compromise between workability, mechanical resistance and aesthetical appearance.